Rh1 high activity binding peptides inhibit high percentages of Plasmodium falciparum FVO strain invasion (2013)
Identifying the minimal functional regions of the proteins which the malaria parasite uses when invading its host cells constitutes the first and most important approach in an effective design for a chemically synthesised, multi-antigen, multi-stage, subunit-based vaccine. This work has been aimed at identifying the PfRh1 protein binding regions (residues 1-2580) belonging to the reticulocyte binding-like (RBL or P. falciparum Rh [PfRh]) family implicated in the parasite's alternative target cell invasion routes. Eighteen peptide regions (called high activity binding peptides - HABPs) binding to red blood cells (RBC) were identified in peptides mapped in a highly robust, specific and sensitive receptor-ligand assay. These HABPs were saturable in the experimental conditions assayed here and most had an alpha helix structure. Polymorphism studies revealed that only six of the eighteen HABPs identified had changes at amino acid level amongst the seven P. falciparum strains evaluated. Most HABPs' specific binding became altered when RBC were treated with neuraminidase, chymotrypsin and trypsin, suggesting differing sensitivity for RBC membrane receptors. After ascertaining that the Rh1 gene was transcribed and expressed in late-stage schizonts of the FCB-2 strain, invasion inhibition assays were carried out. When most of these HABPs were assayed in P. falciparum in vitro culture they were able to inhibit high percentages of FVO strain invasion compared to low inhibition percentages observed with the FCB-2 strain. This data shows small Rh1 regions' participation during invasion and suggests that these units should be included in further immunological and structural studies. © 2013 Elsevier Ltd.